Studi Fenenomenologis : Pengalaman Kader Posyandu Bima Kelurahan Sutojayan dalam Menjalankan Program Penurunan Stunting Berdasarkan Perbup No.116 Tahun 2024 - Lalang Alma Lian Dewi; Ulva Roifatul Lailin; Hanik Amaria (Universitas 17 Agustus 1945, 2025)
This study discusses the Experience of Bima Posyandu Cadres in Sutojayan Village in Implementing the Stunting Reduction Program Based on Perbup No. 116 of 2024 of Blitar Regency. The main focus is to understand the extent to which the implementation of this program has been running and the role of Bima Posyandu cadres in implementing the Stunting reduction program at the village level. Using a descriptive qualitative approach, this study describes in depth the experiences and roles of Bima Posyandu cadres. The theory used as an analytical framework is the Phenomenological Study model from Moleong, L. J., This approach focuses on the perceptions, awareness, and subjective meanings of participants based on their direct experiences with an event or condition. The results of the study indicate that the role of Bima Posyandu cadres influences the rate of stunting reduction in Sutojayan Village. Bima Posyandu still faces various obstacles, such as the limitations of mothers who do not understand the concept of a healthy lifestyle and balanced nutrition. Even so, Bima Posyandu cadres continue to strive to make information simpler and easier to understand for mothers of toddlers. This study also highlights the importance of coordination between Bima Posyandu cadres and health workers, local RT/RWs, and support from mothers of toddlers and families so that the stunting reduction program runs effectively. In addition, this study provides important input for Bima Posyandu cadres in improving the quality of services in Posyandu activities.